New Approaches in the Research for Increasing the Productivity of the Cotton Crop in 21st Century under the Global Warming Situation in India - Sundaramurthy, V. T. (International Journal of Bio-resource and Stress Management, 2017)
The cotton is the most important crop and its productivity is likely to be affected in India by the climate change, due to the global warming processes in ensuing decades which has a negative impact on the agriculture, health of mankind and economy of the country. To mitigate the negative impact of the global warming it is suggested to have the current research approach for increasing the yield of the varieties and hybrids along with the new approaches involving the change of the architecture of the plants with determinate growth habit with the lesser number of small sized leaves and efficient utilizer of increasing level of CO2 in the environment, water , fertilizers and ability to with stand the increasing level of the temperature, surface Ozone, drought, flooding and salinity. The degree of pollution at dyeing center and adjoining niches may be reduced by developing varieties and hybrids with high degree of polimerization of fibers.The mankind may be protected from the increasing degree of UV radiation by providing the fabrics made out of the naturally coloured cotton fibers.